Research progress on extracellular vesicles in the renal tubular injury of diabetic kidney disease - Li, Shengjie; Zheng, Shanshan; Li, Jiao; Lin, Sen; Li, Hao; Wang, Ping; Chen, Ping; Ma, Chaoqun; Liu, Yipeng (Frontiers in Endocrinology, 2023)
Diabetic kidney disease (DKD) is a severe microvascular complication of diabetes and is a chronic progressive condition. It is also a common cause of end-stage renal disease (ESRD), which is characterized by proteinuria or a progressive decline in the glomerular filtration rate. Due to their dependence on high-energy and aerobic metabolism, renal tubules are more susceptible to the metabolic disturbances associated with DKD, leading to inflammation and fibrosis. Consequently, tubular injury has become a recent research focus, and significant advancements have been made in studying the role of extracellular vesicles in DKD-associated tubular injury. This review aimed to elucidate the mechanisms and potential applications of different types of extracellular vesicles in tubular injury in DKD to provide new insights for the prevention and treatment of DKD.